Pain, Agitation and Delirium - Ji Man Hong (Journal of Neurocritical Care, 2015)
Pain, Agitation/sedation, and Delirium (PAD) are frequent complications of critical illness and are associated with poor outcome and even impending dementia. In the setting of the general or neurological intensive care unit, pain and agitation can be ignored because these patients are often under special situations, such as decreased mentality, mechanical ventilation, administration of various sedatives, and physical restraint. In addition, they frequent present with clinically significant delirium. We focused on the pathophysiological integration of PAD by targeting outcomes, detection and monitoring, and management strategies using the ‘ABCDE care bundle’.